Identification of the Utilization of Jember Coffee Skin Biocomposite (Coffea Canephora) as a Sound Absorber Using the Tube Method - Enos Lolang; Israel Padang; Intan Duru’ Sarungallo; Jumiarti Andi Lolo; Adewidar Marano Pata’dungan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development of technology and information is in line with the era of society 5.0 which occurs in various fields, especially in terms of infrastructure which of course will lead to high mobility. One of the negative impacts that arise is noise. For that we need a material that can be used as an acoustic material that functions to absorb sound. Coffee waste is one of the agricultural wastes that can be used as an acoustic material. The purpose of this study was to determine the effect of the sound damping coefficient on sound intensity and the mixture of filler and matrix mass fractions that can be used to muffle sound. The tube method with the Sound Level meter feature from Smartphone will be used to determine the value of the sound attenuation coefficient. In this study, the sound intensity used was 60-100 dB, with a mass ratio of filler and matrix used was 80%:20%, 70%:30%, 60%:40%, 50%:50% and the thickness used is 10mm. The results of the study show that an increase in intensity for each sample will show a decreasing coefficient for each sample. This is due to the higher the intensity of the sound, the higher the sound energy will also be greater so that it is more difficult for the sample to absorb